2014
DOI: 10.1063/1.4878842
|View full text |Cite
|
Sign up to set email alerts
|

A study of shear banding in polymer solutions

Abstract: In a recent letter [M. Cromer, M. C. Villet, G. H. Fredrickson, and L. G. Leal, “Shear banding in polymer solutions,” Phys. Fluids 25, 051703 (2013)], we showed the existence of a steady shear-banded velocity profile for a model polymer solution with an underlying monotonic constitutive curve. The driving mechanism is the coupling of the polymer stress to an inhomogeneous concentration profile. To further understand this phenomenon, in this paper we investigate the underlying linear instability as well as prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 57 publications
6
47
0
Order By: Relevance
“…This was first explored in the context of polymeric fluids [53][54][55]. It has recently been studied again in polymers [56,57], and also applied to yield stress colloidal fluids [58,59]. The signature of concentration coupling in the steady state composite flow curve is an upward slope in the "plateau" of the banding regime.…”
Section: A Steady State Bandsmentioning
confidence: 99%
“…This was first explored in the context of polymeric fluids [53][54][55]. It has recently been studied again in polymers [56,57], and also applied to yield stress colloidal fluids [58,59]. The signature of concentration coupling in the steady state composite flow curve is an upward slope in the "plateau" of the banding regime.…”
Section: A Steady State Bandsmentioning
confidence: 99%
“…(i) Polymers are known to be problematic in strong, nonlinear flows in the sense that they have the tendency to display instabilities, i.e., not deform homogeneously [5]. Instabilities in flowing polymers are receiving more and more attention in recent years [6][7][8][9][10]. Controversies between the experimental findings of different groups have in fact been reported [7,10].…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that the effects of slight differences between the flow fields due to, e.g., alignment issues of the flow geometries play a key role for the occurrence of instabilities [7] and this could potentially explain the discrepancies between different studies. The issue remains however open and the current lack of understanding of the experimental conditions for homogeneous flow or shear banding [6][7][8][9][10] leave the issue of experimental and theoretical analysis of polymeric response in strong nonlinear flows wide open [8,9,11]. (ii) The syntheses of model polymers are mainly performed by anionic polymerization high-vacuum techniques resulting in well-defined molecular structures, which however come in very small quantities (typically <1 g) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…From the aforementioned results we can deduce that the rheological response at nominal 2.25 Pa was consistent with a practical yield stress since some results supported that the fluid gel studied was hardly able to flow, while others showed a marked shear rate. This unstable response may be associated with the onset of very shear thinning behaviour when fluid gels are under yield stress and is also indicative of the occurrence of shear banding (also termed shear localization) (Möller et al, 2006), which is favoured by the lack of concentration homogeneity (Cromer et al, 2014). This is relevant for gellan fluid gels on account of their heterogeneous microstructure.…”
Section: Creep-recovery-creep Testmentioning
confidence: 97%